A BALANCED SCORE CARD STUDY ON PERFORMANCE MANAGEMENT SYSTEM WITH SPECIAL REFERENCE TO KELTRON - A CASE STUDY APPROACH - SIMEON S. SIMON AND SHINY GEORGE (International Journal of Marketing and Technology, 2012)
This research identifies strategic objectives based on the goals of the Keltron organization and develops measurement tools and targets for achieving those desired outcomes. Today, we live in a technology-driven world where speed, flexibility, intellectual capital development, and networks have become the basis of value creation even as connectivity and interactive technologies pervade all business activity. In this technology-driven environment, Keltron finds the assimilation, adoption and integration of technology in creating innovative solutions as the very basis of survival. Keltron's success has been in making technology work rather than inventing it. Keltron has been a catalyst in making electronics work in almost every aspect of our daily life, since 1973. Keltron's strength lies in the stable foundation and experience built over the years, its strong human capital, its nation-wide network and its ability to adapt itself to change. With over a 30-year long track record as a manufacturer of sophisticated electronic devices and systems, Keltron presents itself in the global market as a one-stop-shop for manufacturing, system integration, and after-sales-support in India. From being a pioneer in 1973, to the role of a trend-setter today, Keltron has been the catalyst for the development of electronics industry in Kerala. It was an experiment by Government of Kerala and within five years of its inception, Keltron had set up a production centre in every district of the State. More han 5,000 people were engaged directly or indirectly by Keltron for the manufacture of electronic goods. The model of a State-owned electronics corporation was so successful that several other States in India followed suit; launching their own electronics corporations. A quarter century later, Keltron after having contributed substantially to the industrialization of the State, set about transforming Trivandrum, the capital city of Kerala, into one of the major electronics hubs of the country. Today, the city is home to Techno Park, the internationally known technology park where thousands of talented men and women participate in the development of a burgeoning information technology industry. Keltron describes a range of products and large number of employees. Faced by challenges and the requirements to meet with the changing needs of the customer, many companies across the country have adopted the balanced scorecard approach to align their activities with the vision and mission of the organization and government. However, Keltron still uses financial measures as well as total project numbers in evaluating the performance of the team. This case study develops an evaluation framework based on the balanced scorecard methodology and creates a balanced scorecard system to measure the performance of Keltron. This research identifies strategic objectives based on the goals of the organization and develops measurement tools and targets for achieving those desired outcomes. The research concludes a set of recommendations to ensure implementation and successful application of the balanced scorecard system. The Managers were personally interviewed with the help of questionnaire to understand their perceptions on the Balance Score Card approach and their perspectives on whether adopting the Balance Score Card was of benefit to the organization. The statistical tool used is mean square anal ysis. The research ends with the findings, suggestions and recommendations to Keltron Company for managing performance using balanced scorecard in future and for the welfare of the employees.